2023
DOI: 10.3390/antiox12040936
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammation in B-Cell Lymphomas

Abstract: Mature lymphoid neoplasms arise de novo or by the transformation of more indolent lymphomas in a process that relies on the stepwise accumulation of genomic and transcriptomic alterations. The microenvironment and neoplastic precursor cells are heavily influenced by pro-inflammatory signaling, regulated in part by oxidative stress and inflammation. Reactive oxygen species (ROSs) are by-products of cellular metabolism able to modulate cell signaling and fate. Moreover, they play a crucial role in the phagocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…Elevated blood iron and zinc concentrations were inversely associated with the binding affinity of anti‐SARS‐CoV‐2 IgM antibodies, suggesting a potential dampening effect on early humoral responses. This finding aligns with existing evidence linking iron dysregulation to oxidative stress and pro‐inflammatory pathways, 30 known to impair B‐cell function 31 . Additionally, studies in animal models have linked iron overload with pulmonary fibrosis 32 and inhibit the activity and differentiation of T helper cells, 33 which regulate B‐cell proliferation and antibody production through cytokine modulations 34 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Elevated blood iron and zinc concentrations were inversely associated with the binding affinity of anti‐SARS‐CoV‐2 IgM antibodies, suggesting a potential dampening effect on early humoral responses. This finding aligns with existing evidence linking iron dysregulation to oxidative stress and pro‐inflammatory pathways, 30 known to impair B‐cell function 31 . Additionally, studies in animal models have linked iron overload with pulmonary fibrosis 32 and inhibit the activity and differentiation of T helper cells, 33 which regulate B‐cell proliferation and antibody production through cytokine modulations 34 .…”
Section: Discussionsupporting
confidence: 81%
“…This finding aligns with existing evidence linking iron dysregulation to oxidative stress and pro-inflammatory pathways, 30 known to impair B-cell function. 31 Additionally, studies in animal models have linked iron overload with pulmonary fibrosis 32 and inhibit the activity and differentiation of T helper cells, 33 which regulate B-cell proliferation and antibody production through cytokine modulations. 34 These observations collectively suggest that iron could exacerbate viral infection and hinder humoral responses in COVID-19 at certain concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming with the above report that the presence of genetic aberrations, in the absence of interactions with the environment, are not sufficient to result in complete malignant transformation of the cell [137], several general population studies have shown that some translocations, such as t (14,18), are also present in lymphocytes from individuals without lymphoproliferative disorders [138].…”
Section: Oxidative Stress In Lymphomasupporting
confidence: 70%
“…It has been seen that the polymorphism (Ser608Leu) of the NOS2A gene, which codes for inducible nitric oxide synthase (iNOS), determines a greater enzymatic activity and subsequent increase in nitric oxide (NO) [ 144 ]; this polymorphism has been found in many cases of NHL, particularly in subtypes DLBCL and FL. Moreover, a statistically significant association has been identified between B-cell lymphomas and the polymorphism of manganese superoxide dismutase (SOD2 Val16Ala) [ 137 , 143 ]. Other studies have demonstrated an association between NHL and myeloperoxidase (MPO) and glutathione peroxidase (GPX1) polymorphisms; a correlation was seen between FL and MPO (642G > A) and between marginal zone B-cell lymphoma (MZL) and GPX1 (Ex1-226C > T) [ 145 , 146 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the AA pathway and inflammation in the pathogenesis and progression of B-cell lymphomas including DLBCL has been increasingly recognised [78]. Interestingly, while tumour cells derived from 85% of Hodgkin lymphomas expressed 15-LOX 1, the enzyme was not detected in any of the ten biopsies that represented nine different subtypes of NHL, which makes 15-LOX 1 a candidate biomarker to distinguish Hodgkin from NHL [79].…”
Section: Discussionmentioning
confidence: 99%